Centenarians' End‐of‐Life Thoughts and Plans: Is Their Social Network on the Same Page?. Issue 7 (22nd May 2018) - Boerner, Kathrin; Kim, Kyungmin; Kim, Yijung; Rott, Christoph; Jopp, Daniela S.
Abstract : Objectives: To explore how centenarians think about and plan for the end of life (EOL) and to what extent their primary contacts (proxy informants) are aware of these thoughts. Design: Population‐based study with semistructured in‐person interviews. Setting: Defined geographical region approximately 60 km around Heidelberg, Germany. Participants: Subsample drawn from the larger study of centenarians (N = 78) with data on centenarians' EOL thoughts from the centenarian and the proxy informant. Measurements: Centenarians reported on their thoughts about the EOL, perception of the EOL as threatening, longing for death, engagement in any EOL planning, and type of EOL plan (will, living will, healthcare surrogate) in place. Proxy respondents answered the same set of questions based on what they thought the centenarians' perspective was. Results: In nearly half of cases, proxies misjudged whether the centenarian thought about EOL. Although only few centenarians perceived the EOL as threatening, and approximately one‐quarter reported longing for death, proxies overestimated centenarians' reports on the former and underestimated the latter. Proxies reported more centenarian EOL planning than centenarians themselves. Conclusion: Even though enrolled proxies were mostly persons very close to the centenarian, many of them did not seem to be well informed about the centenarians' thoughts and plans regarding the EOL, suggesting a lack of communication between centenarians and social network members in this respect. Healthcare professionals should be aware that, even for very old adults approaching the end of their lives, discussions about EOL and EOL planning may need to be actively encouraged and supported.